Temporal Rainfall Distribution Characteristics at Tura, Western Meghalaya - RAY, LALA I.P.; BORA, P. K.; SINGH, A. K.; SINGH, RAM; SINGH, N. J.; FEROZE, S. M. (Indian Journal of Hill Farming, 2014)
Western Meghalaya is one of the major rainfed- rice grown areas of Meghalaya, India. Tura, the headquarter of West Garo Hills district of Meghalaya, is falling under mild extremely wet agroclimatic zone with an annual rainfall of 4,851.5 mm with 113 numbers of rainy days [average of 24 years (1984-2007) daily rainfall data]. Rainfall analysis with advanced statistical methods can be used for crop planning, land water management, water harvesting, aquaculture and floriculture planning etc. The analysis of 24 years (1984-2007) daily rainfall data of Tura, Meghalaya has been carried out. Monsoon rainfall contributes more than 70% of average annual rainfall. Weekly rainfall is more than 100 mm and 3 rainy days from 16th to 40th standard meteorological week, however, for 1st to 15th and 43rd to 52nd week the probability of getting rainfall is zero.